The effect of PON1 enhancers on reducing acetylcholinesterase inhibition following organophosphate anticholinesterase exposure in rats. (2nd October 2015) - Meek, Edward C.; Chambers, Howard W.; Pringle, Ronald B.; Chambers, Janice E.
Abstract: Novel nucleophiles, a series of substituted phenoxyalkyl pyridinium oximes, have been previously shown by our laboratories to enhance in vitro paraoxonase 1 (PON1)-mediated degradation of a sarin surrogate (nitrophenyl isopropyl methylphosphonate, NIMP) and a VX surrogate (nitrophenyl ethyl methylphosphonate, NEMP). Five of the most efficacious of these nucleophiles were tested in rats for their ability to reduce the level of acetylcholinesterase (AChE) inhibition in brain and peripheral tissues following exposure to NIMP or NEMP. Following simultaneous administration of a nucleophile plus surrogate (at 3 dosages yielding about 10–50% AChE inhibition in the brain at 15 min), all five nucleophiles reduced the AChE inhibition in the brain at all 3 dosages, and reduced peripheral AChE inhibition at the lowest dosage. Protective effects were seen for only a short period of time, i.e., 15 min. Even though these nucleophiles are oximes, they are not effective AChE reactivators so it is unlikely that the resultant decreases in AChE inhibition are from appreciable AChE reactivation. It is likely that the protective effects seen are, at least in part, the result of enhancement of PON1-mediated surrogate degradation, an unprecedented mechanism of therapy that has the potential to be developed into a nerve agent countermeasure.